Solar-assisted gasification of agriculture residues for green hydrogen production - Deshmukh S.; Santhosh R. (My University, 2025)
The present study proposes a novel way of green hydrogen (H2) synthesis by steam – air biomass gasification assisted by solar energy. In view of environmental problems arising due to stubble burning of agricultural residues in India, bagasse, rice straw and wheat straw are selected as biomass samples. Biomass gasification process is simulated in ASPEN Plus software and then effects of gasification temperature (Tg), equivalence ratio (ER) and steam – to – air mass ratio (S/A) on molar H2 content of producer gas (MHC), higher heating value of producer gas (HHV) and cold gas efficiency (CGE) are studied. The process is optimized using Response Surface Methodology (RSM). It is found that Tg=800 °C – 900 °C, ER=0.2 and S/A=1.8–2.2 are optimum ranges to maximize MHC, HHV and CGE, yielding about 40 % MHC, 6 MJ/kg HHV with 80 % CGE. At optimum operational conditions, steam required for steam-air gasification of a 15 kWth gasifier is calculated. This steam is superheated by solar tower. Total heliostat area requirement is calculated to be 40 m2–65 m2 for different input temperatures of superheated steam (Ts) during steam-air gasification. © 2023 Elsevier Ltd